Fibrin‐specific poly(N‐isopropylacrylamide) nanogels for targeted delivery of tissue‐type plasminogen activator to treat thrombotic complications are well tolerated in vivo - Emily P. Mihalko; Kimberly Nellenbach; Manasi Krishnakumar; Nina Moiseiwitsch; Jennifer Sollinger; Brian C. Cooley; Ashley C. Brown (Wiley, 2022)
Abstract Targeted drug delivery for maintaining blood fluidity can reduce the risks associated with systemic anticoagulants that can lead to off‐target bleeding. Recently, there has been much interest in targeted delivery of tissue‐type plasminogen activator (tPA) for treating thrombotic complications. The work presented here characterizes a fibrin‐specific nanogel (FSN) design for targeted delivery of tPA to treat thrombotic complications. Fibrin binding and clot degradation were characterized in vitro, and animal models of thrombosis were used to examine nanogel effects on coagulation parameters. In vitro assays showed tPA‐FSNs attach to fibrin in a dose‐dependent manner independent of tPA loading. In animal models of thrombosis, including an electrolytic injury to monitor clot properties in real time, and a lipopolysaccharide‐induced disseminated intravascular coagulation (DIC) animal model, tPA‐FSNs modulated fibrin/fibrinogen and platelet incorporation into clots and at optimized dosing could recover consumptive coagulopathy in DIC. Distribution of unloaded and tPA‐loaded FSNs showed potential clearance of tPA‐FSNs after 24 h, although unloaded FSNs may be retained at sites of fibrin deposits. Maximum tolerated dose studies showed tPA‐FSNs have minimal toxicity up to 20 times the optimized therapeutic dose. Overall, these studies demonstrate the therapeutic efficacy of targeted fibrinolysis for systemic microthrombi and begin to evaluate key translational parameters for tPA‐FSN therapeutics, including optimal tPA‐FSN dosage in a DIC rodent model and safety of intravenous tPA‐FSN therapeutics.